Effects of cocoa extract and a multivitamin on cognitive function: A randomized clinical trial - Laura D. Baker; JoAnn E. Manson; Stephen R. Rapp; Howard D. Sesso; Sarah A. Gaussoin; Sally A. Shumaker; Mark A. Espeland (2022)
Abstract Introduction Dietary supplements are touted for cognitive protection, but supporting evidence is mixed. COSMOS‐Mind tested whether daily administration of cocoa extract (containing 500 mg/day flavanols) versus placebo and a commercial multivitamin‐mineral (MVM) versus placebo improved cognition in older women and men. Methods COSMOS‐Mind, a large randomized two‐by‐two factorial 3‐year trial, assessed cognition by telephone at baseline and annually. The primary outcome was a global cognition composite formed from mean standardized (z) scores (relative to baseline) from individual tests, including the Telephone Interview of Cognitive Status, Word List and Story Recall, Oral Trail‐Making, Verbal Fluency, Number Span, and Digit Ordering. Using intention‐to‐treat, the primary endpoint was change in this composite with 3 years of cocoa extract use. The pre‐specified secondary endpoint was change in the composite with 3 years of MVM supplementation. Treatment effects were also examined for executive function and memory composite scores, and in pre‐specified subgroups at higher risk for cognitive decline. Results A total of 2262 participants were enrolled (mean age = 73y; 60% women; 89% non‐Hispanic White), and 92% completed the baseline and at least one annual assessment. Cocoa extract had no effect on global cognition (mean z‐score = 0.03, 95% CI: ‐0.02 to 0.08; P = .28). Daily MVM supplementation, relative to placebo, resulted in a statistically significant benefit on global cognition (mean z = 0.07, 95% CI 0.02 to 0.12; P = .007), and this effect was most pronounced in participants with a history of cardiovascular disease ( no history : 0.06, 95% CI 0.01 to 0.11; history : 0.14, 95% CI ‐0.02 to 0.31; interaction, nominal P = .01). Multivitamin‐mineral benefits were also observed for memory and executive function. The cocoa extract by MVM group interaction was not significant for any of the cognitive composites. Discussion Cocoa extract did not benefit cognition. However, COSMOS‐Mind provides the first evidence from a large, long‐term, pragmatic trial to support the potential efficacy of a MVM to improve cognition in older adults. Additional work is needed to confirm these findings in a more diverse cohort and to identify mechanisms to account for MVM effects. Highlights COSMOS‐Mind was a large simple pragmatic randomized clinical trial in older adults conducted by mail and telephone. The trial used a two‐by‐two factorial design to assess treatment effects of two different interventions within a single large study. We found no cognitive benefit of daily cocoa extract administration (containing 500 mg flavanols) for 3 years. Daily multivitamin‐mineral (MVM) supplementation for 3 years improved global cognition, episodic memory, and executive function in older adults. The MVM benefit appeared to be greater for adults with cardiovascular disease.